Digital Heritage and Societal Development - Edward Sankowski; Betty Jean Harris (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Aim of study. In their book, Digital Heritage, Karol Król and Józef Hernik have made a unique and major contribution to the history of digital technology, and, coupled with that, to identifying the significance of “digital heritage” for societal development, in particular in relation to developmental improvements in environmental processes. The aim of this article is to identify some main scientific, technological, and logical features of the book’s account of what digital heritage is as part of environmental processes.